Correlation Between Immune-Related Adverse Events and Prognosis in Hepatocellular Carcinoma Patients Treated With Immune Checkpoint Inhibitors - Xu, Shuo; Lai, Ruixue; Zhao, Qian; Zhao, Pandong; Zhao, Ruili; Guo, Zhanjun (Frontiers in Immunology, 2021)
Background Immune-related adverse events (irAEs) caused by immune checkpoint inhibitors (ICIs) were associated with clinical benefit in cancer patients of melanoma, a lung cancer. In the present study, we investigated the correlation between irAE and ICI efficacy in hepatocellular carcinoma (HCC) patients. Methods We divided the HCC patients who received the anti-PD-1 antibody into two groups as irAE group and non-irAE group according to the National Cancer Institute Common Terminology Criteria for Adverse Events ver. 4.03. The treatment efficacy of ICIs was evaluated with objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS). Result Of the 65 HCC patients who received the anti-PD-1 antibody (monotherapy or combined with targeted medicine), median PFS in the irAE group was superior to that in the non-irAE group (302 days vs. 148 days, p = 0.004). Median OS in the irAE group was also better than that in the non-irAE group (374 days vs. 279 days, p = 0.038). Although the statistical difference for DCR in the irAE group and non-irAE group was not reached, the DCR of the irAE displayed a trend better than that of the non-irAE group (41.20% vs. 20.80%, p = 0.118). Multivariate analysis also demonstrated that the non-irAE group (HR = 6.410, 95% CI: 1.404 to 29.275) was associated independently with the poor prognosis. Conclusions Development of irAEs was associated with clinical benefit for HCC patients who were treated with immune checkpoint inhibitors; irAE, particularly low-grade irAE, was a predictable marker for better ICI treatment efficiency in HCC patients.